Strain differences in Shope fibroma virus. An immunopathologic study. - Strayer, D. S. (1984)
The pathogenic effects of plaque-purified Boerlage and Patuxent strains of Shope fibroma virus (SFV) in neonatal rabbits are compared with results of previous reports which used nonpurified SFV. Clinically, the Boerlage strain produced large tumors; whereas the same dose of Patuxent strain SFV induced much smaller tumors locally. Neither virus caused metastatic or extensively invasive local spread in our study. Some Patuxent recipients died of respiratory infections prior to sacrifice. However, both groups of rabbits handled the tumor well; the tumor began regressing 15-20 days after inoculation. Histologically, the tumors produced by those viruses were identical. Patuxent strain recipients were otherwise normal. Boerlage strain recipients showed increased persistence of extramedullary hematopoiesis and scattered foci of parenchymal necrosis in their livers. They also showed considerable cell death in thymic lobules. In rabbits given Patuxent strain SFV, virus antigens were detected only in the tumor by immunohistologic examination. Boerlage viral antigens were found in the tumor and overlying skin. We also detected virus systemically in Boerlage recipients: it was present in fixed tissue phagocytes in the spleen and liver and also in parenchymal cells of the lungs, liver, and kidney. Boerlage strain SFV recipients also showed detectable virus in their thymus, both at the periphery of the thymic lobules and in the connective tissue separating thymic lobules from each other. Despite the disseminated nature of the infection, rabbits that received the latter strain fared as well as those receiving Patuxent strain SFV.